Insulated Sandwich Panels from Natural Rubber and Rubber Wood - Phohchuay, Parntip; Khongtong, Sureurg (Science Essence Journal, 2018)
ABSTRACT The focus of this research was to study the properties of insulated sandwich panels created from natural rubber as a core and rubber wood strands as surface layers in order to introduce more sustained components for construction materials. This panel was fabricated under the hot compression at the temperature of 150 ºC to trickle a blowing agent mixed in rubber compounds to decompose and yield amounts of gas leading to a porous rubbery core. This brought the density of this product to reach 410-550 kg/m3 which was about four times lighter than that of the brick and concrete walls. This density was even lower than that of the commercial light weight panels for three times while the strength of the panel from this research was about two times greater. It was also found that the panel from this research revealed the value of thermal conductivity at 0.07-0.08 w/mK which was drastically lower than that of the brick and concrete walls for sixteen times as well as lower than that of the commercial light weight panels for almost two times. Moreover, this panel displayed the value of sound transmission lost at 35-80 dB which was about two times better than that of the wall materials used currently.